2016
DOI: 10.1187/cbe.15-12-0267
|View full text |Cite
|
Sign up to set email alerts
|

Using Student Writing and Lexical Analysis to Reveal Student Thinking about the Role of Stop Codons in the Central Dogma

Abstract: Computerized lexical analysis paired with human scoring was used to explore student ideas about the effect of a stop codon mutation on replication, transcription, and translation. It was found that student ideas about one process can affect their understanding of subsequent and previous processes, leading to mixed conceptual models of the central dogma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…Lexical analysis has shown promise for evaluating constructed-response items through computer scoring. 18,[47][48][49][50][51] Over 100 items are available in the Automated Analysis of Constructed Response (AACR) library; 52 most items in the library, though, target biology concepts. 18 We remedied the burden of assessing student understanding of the Lewis acid-base model by capitalizing on the AACR project's lexical analysis methodology; we developed a predictive model for scoring written explanations of an acid-base proton-transfer reaction with 86% accuracy for "use" or "non-use" of the Lewis acid-base model in the response.…”
Section: Lexical Analysis Of Constructed-response Items As a Formativmentioning
confidence: 99%
“…Lexical analysis has shown promise for evaluating constructed-response items through computer scoring. 18,[47][48][49][50][51] Over 100 items are available in the Automated Analysis of Constructed Response (AACR) library; 52 most items in the library, though, target biology concepts. 18 We remedied the burden of assessing student understanding of the Lewis acid-base model by capitalizing on the AACR project's lexical analysis methodology; we developed a predictive model for scoring written explanations of an acid-base proton-transfer reaction with 86% accuracy for "use" or "non-use" of the Lewis acid-base model in the response.…”
Section: Lexical Analysis Of Constructed-response Items As a Formativmentioning
confidence: 99%
“…This was necessary to alleviate extraneous variables, such as instructor, in the study. Prior research has shown that 350 or more student responses are necessary to build statistically significant predictive models (11,25). This study was done at the beginning of our data collection, and we will continue to collect data to build statistical models that predict human scoring of these two questions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Weerts and Cabrera [84] documented factors that influenced the type of civic engagement college students engaged in (superengager, apolitical-engager, social-cultural engager, and nonengager). Finally, Prevost and colleagues [85] used multinomial regression to analyze student understanding of biology concepts by moving beyond simply categorizing student responses as right or wrong and allowing for different types of incomplete understanding.…”
Section: E Multinomial Regression 1 When To Use Multinomial Regressionmentioning
confidence: 99%